Urban Growth and Sanitation Condition of Damak Municipality - Dahal, Kedar (Himalayan Review, 2011)
Available with fulltext. Key words: Urban Growth; Sanitation; Population Growth The Himalayan Review Vol. 24-28 1993-1997 Page: 76-84 Uploaded date: 15 June, 2011